Robustness of inter-individual differences in slow wave sleep for daytime sleep periods after total sleep deprivation with or without caffeine administration: potential implications for around-the-clock operations. (2nd October 2020) - Erwin, Julie A.; Skeiky, Lillian; Satterfield, Brieann C.; Paech, Gemma M.; Layton, Matthew E.; Van Dongen, Hans P. A.; Hansen, Devon A.
ABSTRACT: There are large inter-individual differences in slow wave sleep, which constitute a trait or phenotype. We investigated whether the manifestation of this trait is impacted by daytime sleeping after sleep deprivation, and to what extent it is robust to prior caffeine intake. N = 12 subjects underwent three 48 h periods of total sleep deprivation with different caffeine dosing regimens. There were significant, considerable, and robust inter-individual differences in slow wave sleep across nighttime sleep opportunities before, and daytime sleep after, total sleep deprivation, regardless of caffeine dosing. The robustness of this phenotype may have functional implications for individuals in around-the-clock operational settings.